Draft Genome Sequences of Clinical and Environmental Isolates of Aspergillus tamarii from Colombia (2020)
ABSTRACT : Aspergillus is a very diverse genus of fungi that are common in the environment and can affect human health. Here, we report the draft genome sequences of two Colombian isolates of Aspergillus tamarii, an emerging pathogenic species. One isolate was obtained from an infected patient and the other from the environment in a hospital.